Percutaneous Hip Arthroscopy in the Treatment of Femoroacetabular Impingement Syndrome - Nicholas J. Lemme MD; Eric Y. Hu BS; Jesus E. Cervantes BS; Shane J. Nho MD, MS (Video Journal of Sports Medicine)
Background: Femoroacetabular impingement syndrome (FAIS) is a common condition in young adults that causes groin pain and predisposes patients to labral tears. Hip arthroscopy has become the gold standard in the treatment of FAIS and involves labral repair and osteoplasties to address any bony impingement. Traditionally, hip arthroscopy begins with access to the central compartment, followed by osteoplasties in the peripheral compartment (PC). However, initiating with the PC using percutaneous instrumentation has emerged as an effective alternative. This approach preserves capsular integrity and may simplify the procedure, especially when employing a periportal capsulotomy. Indications: Indications for the percutaneous approach include the treatment of FAIS and/or labral tears, especially in the context of tight/smaller joint spaces. Technique Description: This approach involves PC work first through the modified mid-anterior portal and anterolateral portal utilizing a 5.5-mm arthroscopic burr. Minimizing the degree of capsulotomy during this step allows for improved visualization due to decreased fluid loss. Following femoroplasty, a distal anterolateral portal can be created to address any labral tears without the need for further capsulotomy. Finally, capsular plication is performed to close any periportal incisions within the capsule. Results: The percutaneous approach with PC work first allows for a less invasive capsulotomy and femoroplasty in the setting of FAIS. Discussion/Conclusion: Percutaneous hip arthroscopy can be an effective capsular preserving technique that can lead to positive patient rehabilitation and functional outcomes. Performing the femoroplasty first with percutaneous instrumentation can mitigate the need for traditional capsulotomies. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.